2022
DOI: 10.1073/pnas.2118126119
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide CRISPR knockout screen identified PLAC8 as an essential factor for SADS-CoVs infection

Abstract: Significance A potential outbreak of swine acute diarrhea syndrome coronavirus (SADS-CoV) in the human population could be devastating. Using genomewide CRISPR knockout screening, we identified the placenta-associated 8 protein (PLAC8) as an essential host factor for SADS-CoV infection, uncovering a novel antiviral target for CoV infection. The PLAC8-related pathway may also have implications for other CoV infections. Given the ability of SADS-CoV to infect human primary cultures without adaptation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 69 publications
1
20
0
Order By: Relevance
“…Similarly, it has been shown that deletion of the retromer component VPS29 inhibits SARS‐CoV‐2 infection and results in entrapment of VSV/SARS‐CoV‐2 chimeric viruses in the endosomes and the loss of endosomal cathepsin activity (Poston et al , 2022). It is worth noting that, during the final round of revision of this work, another genome‐wide CRISPR screen has identified PLAC8 as an essential factor for swine acute diarrhea syndrome coronavirus (SADS‐CoV), an alpha‐CoV‐1 virus closely related to beta‐CoVs (Tse et al , 2022). Interestingly, they also concluded that most likely PLAC8 participates in vesicle trafficking in the early stages of the SADS‐CoV life cycle, but it does not affect virion binding or endocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it has been shown that deletion of the retromer component VPS29 inhibits SARS‐CoV‐2 infection and results in entrapment of VSV/SARS‐CoV‐2 chimeric viruses in the endosomes and the loss of endosomal cathepsin activity (Poston et al , 2022). It is worth noting that, during the final round of revision of this work, another genome‐wide CRISPR screen has identified PLAC8 as an essential factor for swine acute diarrhea syndrome coronavirus (SADS‐CoV), an alpha‐CoV‐1 virus closely related to beta‐CoVs (Tse et al , 2022). Interestingly, they also concluded that most likely PLAC8 participates in vesicle trafficking in the early stages of the SADS‐CoV life cycle, but it does not affect virion binding or endocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…The sequence alignment of duck PLAC8 with homologs from mammals, avian species, and piscine counterparts revealed 9 conserved cysteine residues, which comprised 3 conserved CXXC domains, including 48 CXX 51 C, 93 CXX 96 C, and 96 CXX 99 C. It has been reported that knockout of PLAC8 abolishes swine acute diarrhea syndrome coronavirus ( SADS-CoV ) infection in vitro. However, viral infection was restored in PLAC8-knockout cells after complementation with PLAC8 from other species, including humans, rhesus macaques, mice, pigs, pangolins, and bat ( Tse et al, 2022 ). The conserved CXXC domain, which plays an important role in substrate recognition and binding ( Rissoan et al, 2002 ; Bai et al, 2014 ), may have contributed to the successful complementation of PLAC8 from different species in SADS-CoV-infected host cells.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, the strongest DMR observed in exhausted monocytes was hypomethylation in the promoter and intronic enhancer regions of Plac8 ( Fig 1G ). Plac8 upregulation has been identified as a top marker for monocyte dysregulation in scRNA-seq datasets collected from both sepsis and severe Covid-19 patients, and its role as an autophagy-linked plasma and lysosomal membrane protein is believed to be essential for SARS-Cov2 infection (Reyes et al , 2020; Schulte-Schrepping et al , 2020; Ugalde et al , 2022; Tse et al , 2022). Taken together, the extent of differential methylation at so many sites of immune significance highlights the critical role of 5mC as a regulator of monocyte exhaustion.…”
Section: Resultsmentioning
confidence: 99%